Forced convection boundary layer slip flow over a permeable plate in a Darcy-Forchheimer porous medium - Abu Bakar, Shahirah; Md. Arifin, Norihan; Md. Ali, Fadzilah; Nazar, Roslinda (Pushpa Publishing House, 2014)
The problem of steady forced convection boundary layer flow and heat transfer of an incompressible fluid past a permeable plate embedded in a Darcy-Forchheimer porous medium is studied. Velocity and thermal slips are considered instead of no-slip conditions at the boundary. The governing partial differential equations are converted into ordinary differential equations by similarity transformation, which are then solved numerically using the shooting method. The important features of the flow and heat transfer characteristics for different values of porous permeability, suction or injection and slip parameters are analyzed and discussed. The results for the skin friction coefficient, the local Nusselt number, the velocity profile as well as the temperature profile are presented for different values of the governing parameters.